Zakat gaji: suatu kajian terhadap isu al-Hawaij Alasliyyah dalam pelaksanaan di institusi zakat di Malaysia - Mat Isa, Muhammad Pisol; Husni, Ahmad; Abu Bakar, Zulqarnain (Universiti Sains Islam Malaysia, 2024)
Salary is a big portion of zakat collection in Malaysia today, it contributes almost 70 percent of total collection of zakat institutions yearly, the issue of zakat on salary has been discussed by scholars since the those days of sahabah and tabi’in until today. Among the issues are hawl, nisab and al-hawa’ij al-asliyyah. For the case of al-hawa’ij al-asliyyah the practice of zakat institution in Malaysia is to directly convert the exempted amount of personal, spouse and children, which is performed by Lembaga Hasil Dalam Negeri (LHDN), the practice has raised a question among scholars, they argue whether the exempted amounts are exactly representing the costs of al-hawa’ij al-asliyyah which are required by shariah. This paper aims to explore the perception of shariah on al-hawa’ij al-asliyyah with the specific items which has been discussed in classical fiqh and investigate the suitable items which is currently customized in daily life. The study applied a library research methodology by gathering the data from classical fiqh which investigated the opinions of scholars across of four major mazahib, the analysis of the data was done through document analysis and only the selected opinion was considered. The study found that the Hanafi Jurists among those scholars who strongly propagate the inclusion of Hawa’ij al- Asliyyah in zakat calculation, the idea is about to serve the meaning of being wealthy and rich where the group has first to fulfil their basic need before paying the zakat, the study also found that the suitable amount to be exempted for al-hawa’ij al-asliyyah should be referred to the standard used in CPI (Consumer Price Index) for the current application in Malaysia, the amount should be flexible in order cater the unexpected need such as hospitality, education and others.